2015
DOI: 10.1080/10538712.2015.1001473
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Child Sexual Abuse on the Self from Adult Narrative Perspectives

Abstract: The impact of child sexual abuse on the adult self is not yet clearly understood. We explored adult perspectives through the use of narrative interviews (N = 30). Three key themes or views of self were identified in all narratives to varying degrees: the worthless self, the self as unknown and the potential/developing self. Ambivalence and tension were present in all narratives. Individuals are challenged to integrate the sexual abuse experience in a constructive way and develop a more coherent perception of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
4
21
0
1
Order By: Relevance
“…(Parry & Simpson, 2016, p. 801). As reported by Krayer et al (2015), a more coherent self was established in some participants. In summary, the impact of learning more about themselves was described by one participant in the research by Chouliara et al (2011) as, "Well I have found myself .…”
Section: Theme 5: Integration-integration Of Selfsupporting
confidence: 66%
See 3 more Smart Citations
“…(Parry & Simpson, 2016, p. 801). As reported by Krayer et al (2015), a more coherent self was established in some participants. In summary, the impact of learning more about themselves was described by one participant in the research by Chouliara et al (2011) as, "Well I have found myself .…”
Section: Theme 5: Integration-integration Of Selfsupporting
confidence: 66%
“…Acceptance of self and self-integration are important parts of the recovery process (Chouliara et al, 2014) as survivors become more congruent with themselves and others and their relationships improved (Arias & Johnson, 2013). As negative beliefs and thought patterns begin to shift, a meaning in life is established along with feelings of agency (Krayer, Seddon, Robinson, & Gwilym, 2015). As distinct as the identified themes appear, the research also suggests a clear interdependence.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Sistemas de significados en torno a la experiencia erótica y los abusos sexuales en la infancia Gwilym, 2015;Saha, Chung, & Thorne, 2011); o en la identificación de las emociones asociadas con la experiencia (Foster & Hagedorn, 2014). Pero se han abordado tangencialmente las interpretaciones que los participantes narran, específicamente sobre los abusos sexuales y la experiencia de atracción y de placer sexual.…”
Section: Introductionunclassified